TAX PLANNING IN TERMS OF THE CHOOSING OF THE DEPRECIATION METHOD OF FIXED ASSETS (CASE STUDY ON JASA TIRTA 1 MALANG) - Winda Aulinda (Jurnal Ilmiah Mahasiswa FEB, 2016)
The research examines how the Indonesian Financial Accounting Standards Report Number 16 (Pernyataan Standar Akuntansi Keuangan / PSAK- 16) is implemented, the extent to which the selection of fixed assets depreciation method influences tax planning, and how such a selection affects the financial reports of  Perum Jasa Tirta (PJT) 1 Malang. This case study applies deskriptive quantitative method. The result of the analysis shows that PSAK-16 has been implemented very wellin PJT-1. The tax planning of the selection  of fixed assets depreciation method, however, is not not optimally adminisitered yet. Whereas, the method selection influences the amount ofdepreciation expense as stated in the company’s profit and loss statement.Key words: Depreciation expense of fixed assets , Depreciation methods, Tax planning, Deferred tax asset.